A PRACTICAL APPLICATION OF ADDITIVE MANUFACTURING TECHNOLOGY IN ORTHODONTIC TREATMENT: CASE PRESENTATION - L.N. SOLDATOVA; E.S. MUZYKA (Avicenna Tajik State Medical University, 2023)
A new method for positioning mini-implants in orthodontic patients with tooth position anomalies (ICD-10 K07.3) using a navigation surgical template is proposed. The template is used to position a mini-implant precisely based on the visualization results of cone beam computed tomography (CBCT), which facilitates safe and dynamic orthodontic tooth movements. CBCT visualization during the initial placement of mini-implants in the most stable position has significantly reduced the risks of premature loss of stability. Proper placement, in turn, leads to the successful completion of treatment using cortical bone support